Sistem Pendukung Keputusan Pemberian Vaksin HPV Untuk Mencegah Kanker Serviks Pada Wanita Dengan Metode TOPSIS - Sefrika, S (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
One thing that can be done to prevent cervical cancer in women is to vaccinate against HPV. However, further research needs to be done on the priority scale of vaccine recipients so that the goal of service cancer prevention can be carried out. The aim of the study was to determine the administration of the HPV vaccine to women to prevent cervical cancer. The research method used is the TOPSIS method. TOPSIS uses alternative criteria so as to get ideal results from the various options offered. The results showed a value of 1.22 for criteria C4, a value of 0.83 for criteria C1, a value of 0.53 for criteria C2 and a value of 0.37 for criteria C3. Suggestions for giving vaccines should be carried out according to priorities, namely sexually active women (C4), married women (C1), adolescents (C2) and children (C3).